Gambaran Penanaman Rasa Percaya Diri Anak Usia Dini oleh Guru di Lembaga PAUD Adzkia III Kelurahan Korong Gadang Kecamatan Kuranji Kota Padang - Latifah Latifah; Ismaniar Ismaniar; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the high self-confidence of early child in PAUD Adzkia III Village Korong Gadang, District Kuranji, Padang City. This research is quantitative descriptive research. The population in this study was 29 teachers. Sampling using cluster random sampling technique obtained 22 people sample from 75% population. Data collection techniques used are questionnaires, while the data collection tool using a questionnaire sheet. The data analysis technique used is the percentage formula. The result of the research shows that 1) the picture of self-confidence planting through the independent aspect given by the teacher to the child looks very good, 2) the picture of confidence planting through positive thinking aspect given by the teacher to the child looks very good, and 3) the picture the cultivation of trust through the brave aspect of expressing the opinion given by the teacher to the child looks very good. Suggestions in this study is expected to the teacher in order to maintain and increase confidence planting in school so that the child's confidence continues to increase.